Informed consent for caesarean section at a nigerian university teaching hospital: patients' perspective (2015)
Background: Caesarean section is one of the commonest obstetrics surgery and has become increasingly safer compared with the early 20th century. The practice of informed consent has also become universally adopted for surgical procedures. However, with increasing knowledge about ethics and rights, issues on consent is one of the frequent grounds for litigation and malpractice claims. Aims and Objectives: To audit the process of informed consent for emergency and elective caesarean section in a Nigerian tertiary health care setting. Methodology: This was a descriptive cross-sectional study involving 150 patients who had caesarean delivery at the study site within the study period. Results: The mean age of the respondents was 32±1.8 years with 118(79%) of the surgeries being emergency Cesarean sections. The consent for CS were mostly given by the patients (96, 64.0%) and husbands (43, 28.6%). Majority of the respondents 123(81.5%) had the consent obtained in the labour ward with profuse bleeding (86.0%) and blood transfusions (88.7%) being the most commonly discussed risks. Many of the respondents expressed satisfaction with the consent form and felt it was well written (75.3%), attractive (76.0%) and simple to read (75.3%). Conclusion: This study found out that although patients were satisfied with the consent process for caesarean section, only information about major risks was commonly discussed. There is therefore the need for customized and detailed consent forms to be adopted for different surgical procedures.